The future of the Arabic language: globalization and modern problems - Mavlonov, Nurali (The Lingua Spectrum, 2025)
This article analyzes the state of the Arabic language in the context of globalization, modern problems and prospects for future development. The positive and negative effects of globalization on Arabic, in particular the influence of the English language, the spread of “Arabizi”, digital technologies and the role of literary traditions, are examined. Through quotes from classical literature (Quran Karim, Jahiliyya poetry) and modern sources (literature and social networks), the cultural and linguistic significance of the Arabic language is highlighted. The article discusses the possibility of global survival and development of Arabic through education reform, digital content expansion, and international cooperation.